Improvisation of optimization technique and AODV routing protocol in VANET. (2022) - Sindhwani, Manoj; Singh, Rajeshwar; Sachdeva, Amit; Singh, Charanjeet
Abstract: The vehicular ad-hoc network (VANET) is a dynamic network with various applications in intelligent transportation systems. There are several routing protocols for setting up a path between sender node and receiver node. AODV is a reactive routing protocol which broadcast the route request to all neighbouring node and then those nodes will forward the request to their neighbouring nodes. This process helps in selecting the path from sender to receiver. AODV protocol is the best performing routing protocol when number of nodes for communication is more in number. In this research, AODV and Ant Colony Optimization (ACO) technique is applied and data is transmitted. Ant colony optimization algorithm is applied which takes into the initial coordinates of each node. The path which is established using reactive routing protocol has high chances of congestion in the network and also consume large amount of network bandwidth. This research is based on to establish path from source to destination using multicasting approach and also reduce the chances of congestion in the network. It will generate a path with shortest distance and leads to improve throughput, reduce packet loss and delay when compared with the existing protocol.